Implementasi gerakan literasi sekolah dalam membentuk keterampilan membaca permulaan siswa kelas I sekolah dasar - Cintia Irawati Desti Pratiwi; Sukarno Sukarno; Septi Yulisetiani (Didaktika Dwija Indria, 2023)
The goal of this study was to ascertain how the School Literacy Movement was implemented in SD Negeri Bumi I No. 67 Surakarta, how students learned early reading skills during the School Literacy Movement activity in grade I, and how those students' early reading skills changed before and after the School Literacy Movement's implementation. The research method used is a case study approach. Sources of data used in this study were principals, teachers, and grade I students of SD Negeri Bumi I No. 67 Surakarta. Data collection techniques using observation techniques, interviews, and documentation. Validity test using time triangulation and technique triangulation. Data analysis techniques using Miles and Huberman with data reduction, data presentation, and conclusion. The research results obtained were the assessment of the successful implementation of the School Literacy Movement at SD Negeri Bumi I No. 67 Surakarta is quite good. Performance of the School Literacy Movement in class I SD Negeri Bumi I No. 67 Surakarta is in the development stage. There are 3 activities of the School Literacy Movement in forming early reading skills at SD Negeri Bumi I Surakarta, namely reading literacy, numeracy literacy, and literacy. Reading literacy activities have many roles in forming initial reading skills because in practice they can fulfill the indicators of beginner reading skills. This program can be used to develop student qualities and positive habits.